Un succès américain en France : La Case de l’Oncle Tom - Claire PARFAIT (E-REA)
This article examines the early publishing history and the reception of Harriet Beecher Stowe’s anti-slavery novel in France. French translations of the novel were simultaneously serialized in three different Paris dailies, a highly unusual phenomenon in itself. Altogether, eleven translations were published in 1852-1853. Tentative explanations to the popularity of the novel in France can be obtained through an analysis of the contemporary press and of the paratext of the various French editions.